Contextual Variables in Employee Performance-Turnover Relationships - Schwab, Donald P. (Academy of Management Journal, 1991)
A study of 259 tenure-track social science faculty members at a research university found high performers more likely to leave among tenured members but low performers more likely to leave among untenured members. Contextual issues in the university and the external market were considered in explaining these results.